Prototype Development of a Light Sport Aircraft Switched Reluctance Electric Motor - Ravichandran, Sanjeev (My University, 2025)
The increasing global emphasis on reducing greenhouse gas emissions has amplified interest in the electrification of light sport aircraft, particularly for training and recreational purposes. A Switched Reluctance Motor (SRM) is a groundbreaking technology in this field, offering a cost-effective, robust, and efficient alternative to permanent magnet motors. Its straightforward design and ability to perform reliably in elevated temperatures and high-speed make it suitable for aviation applications. While there are challenges surrounding the manufacturing and assembly of SRMs, their strengths position them as a strong contender in the market. The prototype development presented in this thesis focuses primarily on the mechanical design, manufacturing, and assembly of an SRM with a stator outer diameter of 280 mm and a relatively small airgap length of 0.4 mm airgap length between rotor and stator. The proposed SRM is designed to be a direct replacement for a 70 kW Permanent Magnet Synchronous Motor (PMSM) to meet the stringent volume restrictions and operational requirements specific to an aerospace application. This research investigates manufacturing techniques of motor components, precision assembly of rotor and stator cores. Challenges including dimensional accuracy, thermal management, and proper motor component assembly are also discussed. Maintaining mechanical alignment and a small air gap is critical and essential to the motor's efficiency and functionality. This work presents the SRM as an alternative for the electrification of light sport aircraft, contributing to more sustainable aviation solutions.
PROTOTYPE DEVELOPMENT OF A LIGHT SPORT AIRCRAFT SWITCHED RELUCTANCE MOTOR
Keywords: Switched Reluctance Motor; Prototype Development; Light Sport Aircraft